Key genes of the sex pheromone biosynthesis pathway in female moths are required for pheromone quality and possibly mediate olfactory plasticity in conspecific male moths in Spodoptera litura. Issue 1 (24th July 2017) - Lin, X.; Wang, B.; Du, Y.
Abstract: Ninety sex pheromone biosynthesis genes in Spodoptera litura were identified in transcriptome data and were investigated and classified into the following five groups: fatty acid synthase, beta oxidase, fatty acyl‐coenzyme A (CoA) reductase, desaturase and acetyl‐CoA acetyltransferase. Fourteen female‐specific genes were identified through semi‐quantitative PCR, and 15 additional genes had expression levels that were 3‐ to 10‐fold higher in females than in males. The majority of the genes had higher expression levels in the sex pheromone glands. Injection of double‐stranded RNA (dsRNA) against nine selected genes showed that down‐regulation of Desaturase 3 ( Des3 ), Des5 or fatty acyl coenzyme A reductase 17 ( FAR17 ) significantly changed the ratio of the four sex pheromone components (Z, E) ‐9, 11‐tetradecadienyl acetate (Z9E11‐14:Ac), (Z, E)‐9, 12‐Tetradecadienyl acetate(Z9E12–14:Ac), (Z)‐9‐tetradecenyl acetate (Z9‐14:Ac), (E)‐11‐Tetradecenyl acetate(E11–14:Ac). These key genes were differentially expressed in female moths collected from different geographical regions. Furthermore, field bioassays demonstrated geographical variation in the olfactory profile of male moths in response to the different sex pheromone mixtures, which therefore indicates that a significant variation in the sex pheromone components exists in the natural population. Our results suggest that a change in the expression of these key genes, Des3, Des5 and FAR17, in the sex pheromone biosynthesis pathway could change the ratio of the sex pheromone components. We surmise that the differential expression levels of the key genes of the sex pheromone biosynthesis pathway may lead to differential ratios of the sex pheromones in the field. Our field trapping experiment suggested that the change of the ratio of the sex pheromone components may have been adapted by the olfactory system and possibly mediate olfactory plasticity in conspecific male moths.